Developing Symptom Lists for People with Cancer Treated with Targeted Therapies. - Sodergren, Samantha C.; Wheelwright, Sally J.; Fitzsimmons, Deborah; Efficace, Fabio; Sprangers, Mirjam; Fayers, Peter; Harle, Amelie; Schmidt, Heike; Bottomley, Andrew; Darlington, Anne-Sophie; Benson, Charlotte; Bredart, Anne; et al. (Targeted Oncology, 2021)
Background: Targeted therapies (TTs) have revolutionised cancer treatment with their enhanced specificity of action. Compared with conventional therapies, TTs are delivered over a longer period and often have unusual symptom profiles. Patient-reported outcome measures such as symptom side-effect lists need to be developed in a time-efficient manner to enable a rapid and full evaluation of new treatments and effective clinical management OBJECTIVE: The aim of this study was to develop a set of TT-related symptoms and identify the optimal method for developing symptom lists.Patients and Methods: Symptoms from TT treatment in the context of Chronic Myeloid Leukaemia (CML), HER2-positive breast cancer, or Gastrointestinal Stromal Tumours (GIST) were identified through literature reviews, interviews with healthcare professionals (HCPs) and patients, and patient focus groups. The symptom set was then pilot tested in patients across the three cancer diagnoses: The number of items derived from each source (literature, patients, or HCPs) were compared.Results: A total of 316 patients and 86 HCPs from 16 countries participated. An initial set of 209 symptoms was reduced to 61 covering 12 symptom categories. Patient interviews made the greatest contribution to the item set.Conclusions: Symptom lists should be created based on input from patients. The item set described will be applicable to the assessment of new TTs, and in monitoring treatment.